Asuhan Keperawatan Keluarga Dengan Tahap Perkembangan Usia Lanjut Keluarga BPK A Khususnya Ibu Y Dengan Hiperkolesterolemia Terhadap Air Rebusan Daun Salam Untuk Menurunkan Kadar Kolesterol Di Kampung Bayur Pintu 1000 Tangerang - Mardiana Pratiwi; Rina Puspita Sari; M. Hasan Basri; Alfika Safitri (An-Najat, 2023)
Background: the elderly group is a group of people aged 60 years and over. The stage of development of the elderly family is the last stage of this family development starting when one partner dies until both of them die. Hypercholesterolemia is a condition where the amount of blood cholesterol exceeds normal limits, but high cholesterol can cause atherosclerosis which will eventually have an impact on coronary heart disease. Purpose: This case study aims to describe nursing care at the developmental stage of a hypercholesterolemic elderly family by giving bay leaf boiled water to reduce cholesterol levels in Mrs. Y's family in Kampung Bayur Pintu 1000 Tangerang. Method: a case study conducted with observation during 3 meetings with the intervention of giving bay leaf boiled water (Sygium Puolyanthum). Result: the results of the case study found that after the client applied the boiled water of bay leaves for 5 days there was a decrease in cholesterol levels from 300 mg/dl to 235 mg/dl. Conclusion: there is an effect of boiled bay leaves on reducing cholesterol in the elderly. Suggestion: it is hoped that the family will be able to optimize health management in the family for the better and be able to apply bay leaf boiled water therapy to reduce cholesterol levels which has been taught by students which is carried out routinely every day.